Sight unseen [large type] : a novel - Johansen, Iris (Johansen, Iris. Kendra Michaels series., 2014)
"Someone is killing people in ways that mirror Kendra Michaels's most notorious cases and Kendra must come face to face with her most ruthless enemy"--